Resequencing of 558 Chinese mungbean landraces identifies genetic loci associated with key agronomic traits - Han, Xuesong; Li, Li; Chen, Hongwei; Liu, Liangjun; Sun, Longqin; Wang, Xingmin; Xiang, Yantao; Wan, Zhenghuang; Liu, Changyan (Frontiers in Plant Science, 2022)
Mungbean is a warm-season annual food legume and plays important role in supplying food and nutritional security in many tropical countries. However, the genetic basis of its agronomic traits remains poorly understood. Therefore, we resequenced 558 Chinese mungbean landraces and produced a comprehensive map of mungbean genomic variation. We phenotyped all landraces in six different environments. Genome-wide association studies (GWAS) produced 110 signals significantly associated with nine agronomic traits, for which several candidate genes were identified. Overall, this study provides new insight into the genetic architecture of mungbean agronomic traits. Moreover, the genome-wide variations identified here should be valuable resources for future breeding studies of this important food legume.